EFEKTIVITAS PENERAPAN E-KINERJA DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA PADA BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI UTARA - Renald Christo Lembong; sampara lukman; Udaya Madjid (Institut Pemerintahan Dalam Negeri, 2021)
In order to improve the performance of the apparatus and competence of human resources as well as foster creativity and higher work innovation in employees, North Sulawesi Province implements a web-based application called e-Kinerja. Performance appraisal is very influential on the effectiveness of the work of employees at the Regional Personnel Board of North Sulawesi Province. This is to find out whether the performance result of an employee is increasing or decreasing. The low quality of the performance of employees can be caused by several aspects including the not yet optimal main tasks and functions in the work in each field and also the lack of timeless in the implementation of e-kinerja, with an indicator of effectiveness measurement, namely Punctuality which is one of the inhibiting factors in the implementation of e-kinerja. The research method used is a descriptive research method with a qualitative approach by conducting observations, interviews, and documentation of the data sources that have been determined. The result obtained indicate that the application of e-kinerja at the Regional Personnel Agency of North Sulawesi Province has a positive and significant effect on employee work performance and is able to increase job satisfaction obtained